Tick-borne encephalitis. - Dumpis, U; Crook, D; Oksi, J (1999)
Tick-borne encephalitis (TBE) is a zoonotic arbovirus infection endemic to Russia and Eastern and Central Europe. Despite being a common and serious life-threatening disease for which a mass vaccination program was implemented in Austria, there is only limited reference to this disease in the English-language literature. TBE is transmitted to humans usually by the bite of a tick (either Ixodes persulcatus or Ixodes ricinus); occasionally, cases occur following consumption of infected unpasteurized milk. Transmission is seasonal and occurs in spring and summer, particularly in rural areas favored by the vector. TBE is a serious cause of acute central nervous system disease, which may result in death or long-term neurological sequelae. Effective vaccines are available in a few countries. The risk for travelers of acquiring TBE is increasing with the recent rise in tourism to areas of endemicity during spring and summer.